Depth of invasion, size and number of metastatic nodes predicts extracapsular spread in early oral cancers with occult metastases. (June 2018) - Mair, Manish D.; Shetty, Rathan; Nair, Deepa; Mathur, Yash; Nair, Sudhir; Deshmukh, Anuja; Thiagarajan, Shiva; Pantvaidya, Gouri; Lashkar, Sarbani; Prabhash, Kumar; Chaukar, Devendra; Pai, Prathmesh; et al.
Highlights: This study looks into the impact of extracapsular spread (ECS) in early cN0 oral cancer. The incidence of occult nodal metastasis and ECS was 28.5% & 15.3% respectively. Even in metastatic node of size <10 mm and 5 mm, ECS was seen in 45% and 33% respectively. Depth of invasion >5 mm, Metastatic nodal size >15 mm and N2b predicted ECS. ECS significantly impacted overall survival and disease free survival. Abstract: Objective: Presence of extracapsular spread (ECS) significantly decreases survival in oral cancer patients. Considering its prognostic impact, we have studied the incidence and factors predicting ECS in clinically node negative early oral cancers. Materials and Methods: We performed a retrospective chart review of 354 treatment naïve clinically node negative early oral cancer patients operated between 2012 and 2014. Chi-square test and logistic regression were used for identifying predictors of ECS, while cox-regression test was used for survival analysis. Results: The incidence of occult nodal metastasis was 28.5% (101/354). Among them, ECS was seen in 15.3%(54/354) patients. The incidence of ECS in T1 and T2 lesion was 13.4% (21/157) and 16.8% (33/197), respectively. The overall incidence of ECS was 48% and 29% in lymph nodes smaller than 10 mm and 5 mm respectively. We found that tumor depth of invasion (>5 mm; p-0.027) and node (metastatic) size >15 mm (p-0.018) were significant predictors of ECS. p N2b disease was seen in 41/354 (11.6%) of which 31/354 (8.7%) had ECS, i.e. 75.6% of pN2b patients been ECS positive (p-0.000). The 3-year OS of patients without nodal metastasis, nodal metastasis without ECS and nodal metastasis with ECS was 88.4%, 66.9% and 59.2% (p-0.000) respectively. Conclusion: A significant number of patients with metastatic nodal size less than 1 cm have ECS which suggests aggressive behavior of the primary tumor. Thus, elective neck dissection is the only way of detecting ECS in these patients which may warrant treatment intensification.